2016
DOI: 10.1002/hbm.23343
|View full text |Cite
|
Sign up to set email alerts
|

Decreased between‐hemisphere connectivity strength and network efficiency in geriatric depression

Abstract: White matter (WM) lesions have been recognized as a key etiological factor in geriatric depression. However, little is known about the topological pattern changes of WM in geriatric depression in the remitted state (RGD) and its relationship to depressive episodes. To address these questions, we acquired diffusion tensor images in 24 RGD and 24 healthy participants. Among them, 10 patients and 19 healthy controls completed a 1-year follow up. Between-hemisphere connectivity and graph theoretical methods were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 61 publications
5
27
0
Order By: Relevance
“…In the present study, our findings in the white matter network change in LLD patients with or without memory deficits demonstrate that (1) impaired rich-club organization, rich-club connective average strength and assortativity was found in 39 LLD patients compared to 30 HC subjects; (2) compared to LLD-IM patients, LLD-MD patients had disruptive feeder and local connections, especially in cognitive control network (CCN) and corticostriatal circuits; and (3) the alterations of global network properties were accompanied by slight cognitive function change, such as processing speed and memory in the current study. Our findings were compatible with the previous study in the white matter network topological features of LLD patients (Bai et al, 2012 ; Li et al, 2017 ) to some extent, and extend our understanding in the pathological progression of LLD by describing the rich-club properties of LLD-MD patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, our findings in the white matter network change in LLD patients with or without memory deficits demonstrate that (1) impaired rich-club organization, rich-club connective average strength and assortativity was found in 39 LLD patients compared to 30 HC subjects; (2) compared to LLD-IM patients, LLD-MD patients had disruptive feeder and local connections, especially in cognitive control network (CCN) and corticostriatal circuits; and (3) the alterations of global network properties were accompanied by slight cognitive function change, such as processing speed and memory in the current study. Our findings were compatible with the previous study in the white matter network topological features of LLD patients (Bai et al, 2012 ; Li et al, 2017 ) to some extent, and extend our understanding in the pathological progression of LLD by describing the rich-club properties of LLD-MD patients.…”
Section: Discussionsupporting
confidence: 93%
“…This technology has been applied to discover the underlying brain structural changes under neuropsychological diseases (Daianu et al, 2015 ; Gong and He, 2015 ; Schmidt et al, 2017 ). In LLD, the breakdown of global network properties and reductive connectivity between-hemisphere was found in previous studies of the white matter connective network (Bai et al, 2012 ; Li et al, 2017 ). But, there is still largely unknown about the topological organization, especially the role of hub, in LLD.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, LLD compared to HC groups have shown to have impairment in executive function, but no difference in verbal and visuospatial memory (Dybedal et al, 2013), or impairment in attention, and memory functions, but no difference in total cognitive function, processing speed, and executive function (Yue et al, 2015). Other studies have found no differences in the cognitive profile of LLD and HC groups (Alexopoulos et al, 2012), at baseline or over 1 year follow up (Li X. et al, 2017). The discrepancies may be due to differences in the cognitive tests that were used in these studies.…”
Section: Cognitive Impairment In Lld MCI and Ad Is Shared Across Mementioning
confidence: 95%
“…Four DWI studies used network analysis (Li X. et al, 2017;Mai et al, 2017) and graph theory analysis methods (Bai a studies that had reported findings in both rs-fMRI and DWI. b DWI findings were reported in two separate publications.…”
Section: Dwi Studies Using Network and Graph Theory Analysismentioning
confidence: 99%